Decreased B1 and B2 Lymphocytes Are Associated With Mortality in Elderly Patients With Chronic Kidney Diseases - Lin, Jieshan; Tang, Wenfang; Liu, Wei; Yu, Feng; Wu, Yanhua; Fang, Xiaowu; Zhou, Maohua; Hao, Wenke; Hu, Wenxue (Frontiers in Medicine, 2020)
Aim: Loss of renal function is associated with immune deficiency; however, few studies have addressed the role of B lymphocytes in elderly patients with chronic kidney disease (CKD). In this study, we examined the distribution and the relationship of the B lymphocyte subpopulation with clinical outcomes in elderly CKD patients. Methods: In this study, a total of 380 patients (312 CKD patients and 64 non-CKD controls) were recruited. Venous blood samples were analysed by flow cytometry to determine the following B cell subsets: total B cells (CD19+), innate B1 cells (CD19+CD5+) and conventional B2 cells (CD19+CD5-). Correlations between the B cell subsets with clinical features and patient prognosis were analysed. Results: A total of 380 patients (mean age 82.29±6.22 years, 76.3% male) were included. The median follow-up time was 37.0 months (range, 1-109 months); 109 (28.7%) patients died. The main causes of death were infections (59.6%) and cardiovascular diseases (22.9%). Correlation analysis showed that levels of serum creatinine (SCr), blood urea nitrogen (BUN) and CKD were negatively associated with B1 cells. However, lymphocytes, T lymphocytes and the eGFR were positively correlated with B1 cells (all P < 0.05). B2 cells were negatively associated with age, SCr, cystatin C, BUN and CKD, and were positively correlated with haemoglobin, lymphocytes, T lymphocytes, NK cells and eGFR (all P < 0.05). Patient survival was significantly better in patients with B cells > 0.05*10^9/L, B1 cells > 0.02*10^9/L and B2 cells > 0.04*10^9/L. Multivariate Cox regression analysis showed that B1 cells > 0.02*10^9/L (hazard ratio (HR) = 0.502, 95% confidence interval (CI): 0.297-0.851, P = 0.010) and B2 cells > 0.04*10^9/L (HR = 0.536, 95% CI: 0.319-0.901, P = 0.019) were independent protective factors for all-cause mortality. Conclusions: Our results showed that B1 and B2 cells exhibited a significantly negative correlation with the progression of CKD in elderly patients. Moreover, B1 and B2 cells were independent prognostic factors for survival, which indicates that the decrease in B cells may be associated with the progression of kidney diseases. Keywords: B cells, Elderly, Chronic kidney disease, Correlation, Prognosis.